ANALISIS KEBIJAKAN PEMERINTAHAN TENTANG STANDARPROSES PENDIDIKAN AGAMA ISLAM DI MADRASAH (KMA) - Amin Syahputra (HIKMAH: Jurnal Pendidikan Islam, 2025)
This study aims to analyze the KMA policy Number 1503 of 2025 concerning the Standards for Islamic Religious Education Processes in madrasas, especially in the aspect of the Lesson Implementation Plan (RPP). The method used is qualitative with a descriptive approach through documentation and literature studies. The results of the study show that this policy emphasizes the simplification of the RPP administratively but remains oriented towards the quality of studentcentered learning. The RPP is positioned as a contextual, flexible learning design, and integrates Islamic values and 21st-century skills. However, its implementation still faces challenges such as limited teacher competency and infrastructure